Planned Luck: How Incubators Can Facilitate Serendipity for Nascent Entrepreneurs Through Fostering Network Embeddedness. (July 2022) - Busch, Christian; Barkema, Harry
Incubators often play an important role in facilitating networks for entrepreneurs. However, nascent entrepreneurs typically face high uncertainty and goal ambiguity, and which ties could provide the resources needed for achieving the respective goal is often unknown in advance. How do incubators facilitate entrepreneurs' network embeddedness in the context of such uncertainty? Using an explorative case-study approach, we studied an incubator in Kenya, an extreme setting from an uncertainty perspective. Our findings show how in high-uncertainty contexts, a social structure that allows for flexibility can provide the conditions under which unexpected discoveries are enabled, facilitating opportunity-inducing networks.